Stent migration following treatment of pancreatic pseudocyst by cyst gastrostomy. Issue 3 (3rd July 2019) - Smith, Steven; Ramirez, Patrick; Hinds, Alisha; Duggan, Raymond; Ramirez, Jonathan
Abstract: Pancreatic pseudocysts are collections of fluid that form as a complication of pancreatitis. Multiple treatment modalities are available; however, stent placement guided by endoscopic ultrasound has become the therapy of choice due to lower complication rates. We present an uncommon case of self-expandable stent migration following endoscopic drainage of a pancreatic pseudocyst.